Long-term storage of pink pepper essential oil microencapsulated by chickpea protein/pectin complexes: volatile release, antioxidant and antimicrobial activities - Moser, Poliana [UNESP]; Lopes, Nathalie Almeida [UNESP]; Locali-Pereira, Adilson Roberto [UNESP]; Nicoletti, Vânia Regina [UNESP] (Springer Nature, 2024)
Pink pepper essential oil was microencapsulated with chickpea protein (CP) and chickpea protein/pectin (CP-HMP) by spray drying. The reconstitution and storage properties of the powders were evaluated after drying. The impact of microencapsulation in the volatiles release, antioxidant and antimicrobial activity of oil was evaluated during 135 days of storage. CP resulted in more soluble powders (93.52%), CP/HMP resulted in denser powders (0.39 g/mL) while wall material did not influence the wettability. Free pink pepper essential oil (FEO) showed a slight loss of the predominant terpenes (α-pinene, β-pinene, β-mircene, δ-3-carene and D-limonene) after encapsulation. In general, all samples showed an increase in the volatiles release during storage. The evaluation of mass loss showed that FEO had a high release of volatiles, followed by CP and CP-HMP. The antioxidant activity of the FEO decreased (10.8 μg Trolox/mg of oil) after 135 days of storage, whereas the antioxidant activity of CP (14.9) and CP-HMP (14) increased. Both microcapsules presented antimicrobial activity against Bacillus subtilis and Staphylococcus aureus during storage. CP microcapsules had a strong inhibitory effect against the strains tested, and this advantage was even more evident in long-term storage.
Keywords: Bioactive compounds; Microencapsulation; Reconstitution properties; Spray drying; Terpenes; Volatiles release